Study on friction and wear behavior of gray cast iron with different carbon content at different temperatures - Tiefang Chen; Chenggang Wang; Ruifang Yan; Feng Li; Jiandong Wang; Jinguo Wang (Materials Research Express, 2024)
In this paper, we study the friction and wear properties of gray cast iron with different carbon contents at various ambient temperatures. We also examine the failure forms of gray cast iron friction and wear. The research concludes that under low-temperature wear conditions, the graphite in the gray cast iron structure can enter into the interface between the friction pair, have a lubricating effect on the wear surface, and reduce the friction coefficient and wear loss of the gray cast iron material. As the graphite content in the gray cast iron structure increases, its lubrication and protection effects enhance. Consequently, the primary cause of wear failure in gray cast iron is fatigue peeling induced by plastic deformation. Under high-temperature wear conditions, an oxide layer gradually forms on the wear surface. As the experimental temperature increases, the thickness of the oxide layer on the wear surface also increases. When the oxide layer formed on the wear surface reaches a certain level of thickness, the internal expansion stress of the oxide layer increases considerably, causing the oxide layer to peel off and increase the roughness of the wear surface, friction coefficient, and wear loss. Additionally, an increase in the graphite content in the gray cast iron structure makes the surface more prone to oxidation. This leads to increased friction coefficient and wear loss, with the wear failure of gray cast iron primarily caused by the peeling of the oxidation layer.